Odpowiedź:
[tex]a)\ \frac{1}{2}\sqrt{16}+\frac{1}{3}\sqrt[3]{27} = \frac{1}{2} \cdot 4 + \frac{1}{3} \cdot 3 = 2 + 1 = 3[/tex]
[tex]b) \ 4\sqrt{500} + 2\sqrt{20} - 7\sqrt{45} = 4\cdot10\sqrt{5}+2\cdot2\sqrt{5}-7\cdot3\sqrt{5} = 23\sqrt{5}[/tex]
[tex]c) \ 7\sqrt[3]{16} - 5\sqrt[3]{54} = 7\cdot2\sqrt[3]{2} - 5\cdot3\sqrt[3]{2} = -\sqrt[3]{2}[/tex]
[tex]d) \ \sqrt{5}(3\sqrt{5}-2\sqrt{2})-6\sqrt{2}(\sqrt{5}+3\sqrt{2}) = 15 -2\sqrt{10}-6\sqrt{10}-36 = -21 -8\sqrt{10}[/tex]
[tex]e) \ \sqrt{18} : \sqrt{2} - \sqrt[3]{64} : \sqrt[3]{8} = \sqrt{9} - 4 : 2 = 3 - 2 = 1[/tex]
[tex]f) \ \frac{3\sqrt{45}+8\sqrt{125}}{\sqrt{5}} = 3\sqrt{9} + 8\sqrt{25} = 9 + 40 = 49[/tex]